A CLOSE LOOK AT BILINGUALISM RESEARCH IN ASIA - Zen, Evynurul Laily (Indonesian Journal of Applied Linguistics, 2017)
Asia is a ‘homeland’ for bilingualism research in regards to its diversity. It is considered as a vivid research site where there is significant growth of academic areas of exploration. Yet, there are very few scientific attempts to map bilingualism research in an Asian context so far. Thus, I bring the idea of mapping previous works through this literature study by specifically scrutinizing (a) bilingualism research in Southeast Asia, (b) bilingualism research in other parts of Asia, and (c) lessons to learn as a stepping stone to define the future of Indonesian bilingualism. The general data mapping I have explored includes Southeast Asian countries (Malaysia, Singapore, Indonesia, Thailand, and Vietnam) and other parts of Asia (China, India, Israel, and Kazakhstan. The findings from the 33 previous works can be considered as empirical evidence that I will use to portray the research trends in Asia’s bilingualism. The trends show that 19 (55%) works have approached bilingual data from sociolinguistics perspective, whereas the other 14 (45%) have framed their analysis under psycholinguistic approach. Based on the methodological concerns from these works, I propose two major areas of exploration: Family Language Policy (FLP) and trilingual acquisition. FLP in Indonesian is a promising ground, as it brings together issues in language maintenance and shift that instigate a wider aspect of investigation; these aspects include bilingual language dominance, cross language influence, and so forth. Trilingual acquisition, the situation most Indonesian children are growing with, has a potentially significant impact on education, especially where a language curriculum is carefully planned and implemented. In conclusion, this mapping will hopefully shed a light on how bilingualism has academically been very appealing and will continue to fascinate more researchers.